Efektifitas Media Pembelajaran Interaktif Berbasis Adobe Animate CC untuk Meningkatkan Hasil Belajar Peserta Didik - Kasanah, Agustin Arianti Uswatun; Hasan, M. Amin; Mala, Asnal (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2024)
Learning media plays an important role as a tool that facilitates the learning process, increases understanding, and motivates students to be more active in the learning process as well as to achieve learning objectives and solutions to improve learning outcomes. This study aims to determine whether interactive learning media based on Adobe Animate CC for grade IV MI / SD in IPAS subjects can improve student learning outcomes, with a special focus on the material of plant body parts. This research uses quantitative methods with the population and sample of class IV MI Nahdatul Ulama Tambak Sumur Waru Sidoarjo. This study was designed to collect data through pre-test and post-test in experimental and control classes. The data from the students' pre-test and post-test results were then analyzed using the SPSS version 29 program. Adobe Animate CC was used to assess students' abilities both before and after the trial. The results of this study show that grade IV learners improved their learning outcomes with an average of 68.78% before using interactive learning media to 85.51% after using the media, this shows that learners can improve their learning outcomes by using interactive learning media based on Adobe Animate CC.